2016
DOI: 10.1371/journal.pone.0150713
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Seasonality and Treatment of Hospitalized Adults and Adolescents with Influenza in Jingzhou, China, 2010-2012

Abstract: BackgroundAfter the 2009 influenza A (H1N1) pandemic, we conducted hospital-based severe acute respiratory infection (SARI) surveillance in one central Chinese city to assess disease burden attributable to influenza among adults and adolescents.MethodsWe defined an adult SARI case as a hospitalized patient aged ≥ 15 years with temperature ≥38.0°C and at least one of the following: cough, sore throat, tachypnea, difficulty breathing, abnormal breath sounds on auscultation, sputum production, hemoptysis, chest p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
2
12
2
2
Order By: Relevance
“…The independent risk factors for mortality that were identified in this analysis, age ≥ 65 years and ICU admission, are consistent with those found in a limited number of studies reporting risk factors for mortality in all SARI patients [20,24]. Of 1790 adult and adolescent SARI patients in China, age ≥ 65 years was a significant risk factor for severe SARI outcomes (ICU admission or death) [21]. Among SARI patients aged ≥ 5 years in a South African population with high-HIV-prevalence, Cohen et al found that ICU admission was a significant risk factor in bivariate analysis while increasing age was an independent risk factor in multivariate analysis [20].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The independent risk factors for mortality that were identified in this analysis, age ≥ 65 years and ICU admission, are consistent with those found in a limited number of studies reporting risk factors for mortality in all SARI patients [20,24]. Of 1790 adult and adolescent SARI patients in China, age ≥ 65 years was a significant risk factor for severe SARI outcomes (ICU admission or death) [21]. Among SARI patients aged ≥ 5 years in a South African population with high-HIV-prevalence, Cohen et al found that ICU admission was a significant risk factor in bivariate analysis while increasing age was an independent risk factor in multivariate analysis [20].…”
Section: Discussionsupporting
confidence: 88%
“…We can make some comparisons to other studies with the caveat that varying populations, years studied and enrollment methods may affect the findings. The proportion of influenza-positive SARI cases in our study was higher than reported in Kenya (10%) [26] and China (16%) [21], within range of eight African countries (5% in Tanzania to 26% in Madagascar) [19] and slightly lower than New Zealand (23%) [27]. In our surveillance system, the percent of SARI cases positive for an influenza virus varied by year from 5.6% to 20% and likely reflects the influenza activity of the dominant virus that year [11].…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…All these component series have a certain characteristic or type of behavior [19][20][21]. Zt represents the monthly incidence of the diseases.…”
Section: Seasonality Analysismentioning
confidence: 99%
“…2009 pandemisinde yatarak izlenen hastaların çoğu, genç erişkinlerden oluşmaktayken (7); 2009 sonrası SARI tanısıyla takip edilen hastalar için ortanca yaşın 63 yıl olduğu (8) ve 65 yaş üstü hastaların influenza vakalarının %40-61'ini oluş-turduğu bildirilmiştir (8)(9)(10). Çalışmamızda izlenen hasta grubunda ortanca yaş 68 (20-95) yıldı ve olguların %55'i 65 yaş üstü hastalardan oluşmaktaydı.…”
Section: İrdelemeunclassified